School of Geographic Sciences of the National University: contributions to the strategic positioning of the academic unit and the geographic sciences within the context of national development - Rodríguez Soto, Francisco (2024)
From the new perspectives required by geography, the School of Geographic Sciences (ECG) has positioned a strategy of influence with greater presence in various fields. The academic approach is fundamental for positioning and creating reflective spaces in innovation, generation, and transmission of new knowledge. This approach is necessary and present within the public university with a humanistic perspective. However, it is essential to consider the professional dimension of geography as part of the university’s commitment to society. In this university extension effort beyond the National University, the ECG proposes medium- and long-term actions aimed at impacting national development and contributing to the professional and labor fields of its graduates.